Determinants of irregular migration of Ethiopians along the Southern Route: Insights from Kembata migrants to the Republic of South Africa - Megersa, Hailu; Tafesse, Tesfaye (The Greek Review of Social Research, 2025)
This study focuses on understanding the determinants of irregular migration among Ethiopians, specifically examining the case of the Kembata migrant routes to the Republic of South Africa. Data were obtained from a cross-sectional household survey, in-depth interviews and focus group discussions. Descriptive statistics, chi-square tests, binary logit models and thematic analysis were used to analyse the data. Our findings indicate that being a young male, having a large family size and having social networks positively influence household decisions for international migration. Possession of farmland, being employed, and being married have a negative influence on households’ decisions for international migration. The results of this study are expected to contribute to the existing body of literature on Ethiopian migration and provide a better understanding of the complex factors driving irregular migration along the Southern Route.